Analisis Sentimen Komentar Youtube Konferensi Tingkat Tinggi G20 Menggunakan Metode Naive Bayes - Firsttama, Risav Arrahman; Arifiyanti, Amalia Anjani; Kartika, Dhian Satria Yudha (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
In nowadays digital era, social media, especially YouTube, has become a source of information that is easily accessible just from smartphone. YouTube has a lot of video content on display and there are often positive and negative reviews of the 2022 G20 Summit that are irrelevant. The 2022 G20 Summit addresses global issues. The research method in this study used Naive Bayes with a total of 19,215 comment data and Cross Validation with 5 -fold validation. The outcome of this research could determine the accuracy, precision, recall, f1-score of Naive Bayes. The outcome could be enable sentiment predictions in the future using the model that has been built.